String quartets in Beethoven's Europe - November, Nancy (Academic Studies Press, 2022)
"This book is the first detailed study of string quartets in late-eighteenth and early-nineteenth century Europe. It brings together the work of nine scholars who explore little-studied aspects of this multi-faceted genre. Together, this book's chapters deal with compositional responses to Beethoven's string quartets and the prestige of the genre; varied compositional practices in string quartet writing, with a particular emphasis on texture and performance elements; and the reception of Beethoven's string quartets ca. 1800. They include discussion of quartets composed for the amateur and connoisseur markets in Beethoven's Europe; virtuosity, the French Violin School, and the quatuor brillant; the relationship between quartet composers and their audiences during Beethoven's era; and the cross-pollination of quartet styles in Europe's musical centers such as Vienna, Paris, and St. Petersburg"--